Analysis of The Application of Learning Theory of J.B. Bruner in a Counseling Study Counting Operation to Add Whole Numbers - Mutaqin, Ejen Jenal; Muslihah, Neni Nadiroti; Hamdani, Nizar Alam; Sasty, Sri Dewi Febriani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
This study was a qualitative descriptive study design which aims to find out the analysis results of the implementation of Jerome S. Bruner's learning theory in learning concept of addition count operations of whole numbers in the first grade of elementary school. Jerome S. Bruner's learning theory is one of the learning theories that emphasizes the learning process using mental, namely the individual who learns to experience what he is learning for himself, so that the process can be recorded in his mind by his own way. The stages of Bruner's learning theory are: (1) the enactive stage, (2) the iconic stage, and (3) the symbolic stage. Data collection techniques in this study used student worksheets, observation, interviews and documentation. Based on the results of the study, it can be concluded that the process of applying Jerome S. Bruner's learning theory can have a good effect and increase students' understanding and learning ability in learning addition count operations of whole numbers in the first grade of 1 Mekarsari Elementary School.